Inside and Outside the Translation Classroom - Pietrzak, Paulina (Research in Language, 2020)
The article provides a glance at the continuing transformation in the profession of translators and its implications on translator training. The profile of the translatorhas never been unified but nowadays, following the pandemic situation in the year 2020, the profession undergoes a significant shift as a result of the economic situation and the effects of the pandemic restrictions on the condition of the labour market. The widespread use of technology and new requirements involving distance learning call for rethinking the aims of translator training. The primary purpose of the article is to signal the need for adapting translator training to foster better metacognitive skills that help translation students adapt to the evolving market. The article makes an attempt to look at the potential of distance translator training for introducing more professionalization into translator education. Moving outside the regular translation classroom to virtual training environments can in fact entail the learner transformation not only as regards technology immersion but also their autonomy.